The Genetic Architecture of Juvenile Growth Traits in the Conifer Torreya grandis as Revealed by Joint Linkage and Linkage Disequilibrium Mapping - Chen, Wenchong; Yu, Weiwu; Dong, Ang; Zeng, Yanru; Yuan, Huwei; Zheng, Bingsong; Wu, Rongling (Frontiers in Plant Science, 2022)
Despite its high economical and ornamental values, Torreya grandis, a dioecious non-timber coniferous species, has been an underrepresented species. However, the advent and application of advanced biotechnologies have stimulated its genetic research, expected to gain new insight into the genetic architecture of complex traits that may not be detected for other model species. We design an open-pollinated (OP) sampling strategy of T. grandis under which nearly 100 unrelated trees randomly chosen from the species’ natural distribution and their half-sib progeny are simultaneously genotyped. This strategy has proven to be powerful for mapping quantitative trait loci (QTLs) that affect progeny traits by integrating advantages of linkage and linkage disequilibrium (LD) mapping. The recombination of DNA markers from maternal to offspring generations allows a high-density linkage map of 4,203 SNPs covering a total distance of 8,393.95cM to be reconstructed. Recombination events accumulated during T. grandis evolution make it possible to localize progeny trait QTLs to the linkage map at high resolution. From a linkage-LD map, we infer the evolutionary history of T. grandis and each of its QTLs. We identify 13 QTLs for stem basal diameter growth and 4 QTLs for stem height growth in progeny seedlings. The slow decay of QTL-related LDs indicates that these QTLs and their harboring genomic regions are evolutionarily relatively young, suggesting that they can better utilized by clonal propagation rather than through seed propagation. Our OP strategy and results from this strategy could provide useful guidance for genetic studies of other dioecious species.